1999
DOI: 10.1177/00139169921972362
|View full text |Cite
|
Sign up to set email alerts
|

The Correlates of Small-Town Upkeep

Abstract: Although small towns in America differ significantly in terms of how well they are maintained, there has been little scholarly work on what community factors relate to upkeep. In this research, we search for the correlates of town maintenance using data from a unique study of 99 small Iowa towns. The data include visual assessments of the towns, citizen responses to random sample attitudinal surveys, and U.S. census information. When these data are analyzed, the results show that better kept towns are associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
7
0
2
Order By: Relevance
“…During the visit, the researcher completed a lengthy objective survey on the upkeep of the businesses, residences, schools, parks, and churches. If our subjective community-level attractiveness ratings correlate modestly with the Rice and Miller (1999) objective community-level upkeep scores, this would be evidence that the ratings are, indeed, measuring attractiveness. After all, well-kept property is generally considered more attractive than poorly kept property.…”
Section: Community Attractivenessmentioning
confidence: 90%
See 3 more Smart Citations
“…During the visit, the researcher completed a lengthy objective survey on the upkeep of the businesses, residences, schools, parks, and churches. If our subjective community-level attractiveness ratings correlate modestly with the Rice and Miller (1999) objective community-level upkeep scores, this would be evidence that the ratings are, indeed, measuring attractiveness. After all, well-kept property is generally considered more attractive than poorly kept property.…”
Section: Community Attractivenessmentioning
confidence: 90%
“…We can, however, conduct a test to help give us confidence that our attractiveness ratings are similar to the ratings that most other people would give the towns. The test makes use of the community upkeep data collected by Rice and Miller (1999). As noted earlier, these scholars rated 99 small Iowa towns in terms of their upkeep.…”
Section: Community Attractivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we also found empirical evidence against the hypothesis of positive relation between place attachment and neighborhood care. Although a high level of community attachment has been found in wellcared towns of Iowa (United States), high levels of attachment have also been found in deteriorating neighborhoods (Rice & Miller, 1999). For example, Brown and Perkins (1992), Brown et al (2003Brown et al ( , 2004b, and Lewicka (2005Lewicka ( , 2011 have shown that poorly conserved neighborhoods with low socioeconomic status tend to have high levels of attachment.…”
Section: Neighborhood Care and Neighborhood Bondsmentioning
confidence: 99%